THE EFFECTIVENESS OF THE USE OF COOPERATIVE LEARNING MODEL TYPE THINK PAIR SHARE (TPS) ON THE MATHEMATICS PROBLEM SOLVING ABILITY - Diah Candra Wulandari; Sunaryo Sunaryo (Universitas Ahmad Dahlan, 2018)
The learning process centered on teachers has resulted in a lack of mathematical problem-solving ability. This study aims to determine (1) To know the differences of student's ability to solve mathematics problems by using a cooperative learning model of TPS type and students taught using the Direct learning model, (2) Effectiveness of TPS type cooperative learning model compared to Direct learning model. This type of research uses quantitative research methods. This study's population is the students of class VII Semester II Muhammadiyah Junior High School 1 Yogyakarta (SMP Muhammadiyah 1 Yogyakarta) academic year 2016/2017. Sampling was done by random sampling to class, selected class VII F as experiment class, and VII G as control class. The technique of collecting data by a test method. This research instrument is a math problem-solving test in the form of a description problem. Data analysis used was a t-test, normality test using the Chi-Square formula, and homogeneity test using the Bartlet test with a 5% significant level. Hypothesis test in this research uses two parties, t-test and one party t-test with a 5% significant level. Based on the results of this study at a significant level of 5% and degrees of freedom 62, then obtained: (1) count and ttable obtained tcount> ttable, so rejected. Then there are differences in the problem-solving skills of students whom mathematics using the cooperative learning model of TPS type with students who are using the Direct learning model. (2) count and ttable obtained tcount > ttable so rejected. So it can be concluded that the model of cooperative learning TPS type is more effective than the direct learning model to the problem-solving ability of mathematics.